Extensão rural pública: métodos, possibilidades e limites para a transição agroecológica no oeste catarinense - Haverroth, Célio (2012)
This research aims to understand and analyze the strategies used by Public Rural Extension in the West of Santa Catarina, in the perspective of agroecological transition. We characterized six agroecosystems, or family production units, considering the attributes of sustainability, in its dynamic and multidimensional concept. We used, as a methodological strategy, the landmark of systems assessment incorporating natural resource management sustainability indicators (MESMIS), and semi-structured interviews and questionnaires, applied to extensionists of the Company of Agriculture Research and Rural Extension of Santa Catarina (Epagri), and document analysis. It was considered agroecology the field of interdisciplinary knowledge, holistic and seeks hybridization of knowledge for the construction of agricultural systems and rural development. The agroecosystems studied have diverse strategies of resistance to their social reproduction. Regarding socioeconomic relations, is very strong the organization in collaborative networks, production groups, marketing groups and representations of class, as well as interaction with support organizations, whether in the field of family farming, as well as the globalizing market. We also identified some significant issues in common in agroecosystems: a short cycle on marketing is an alternative strategy to the market integration of empires food; the water and soil are natural resources that present problems related to inadequate management; the productive activity has been the milk production, but the sustainability depends on diversification; the tradition in the processing of colonial products is an important basis for the formalization of agribusinesses family farming; the cultural valorization, recreational in rural space, family relationships and the painfulness of labor are issues related to youth rural exodus and to succeed in the production units and; the production for self-consumption is a strong point of agroecosystems, which ensures good quality of food, strengthen community ties, produces local knowledge and represents an important basis for the conversion to sustainable production systems. The public rural extension in the region, roughly, does not address the significant issues above and persists in diffusionists strategies, associated with the model called conservative modernization of agriculture. The demands of the job in rural extension are diversified, leaving little room for interference of farmers in developing of work plans. The role of public rural extension in the region studied, in view of agroecological transition, depends on the approach with other organizations in the field of family farmers who work in rural areas for the formation of a system of information and knowledge with the effective participation of farmers, that meets the real needs of agroecosystems. Is also important redefine the role of contemporary rural extension, to the solution of the problem of work overload, making it agile, present and effective. From the methodological point of view, points to the use of systemic and participatory approaches, based on the principles of dialog, epistemological curiosity, significant themes, questioning and reading the world.